PSYCHOLOGICAL WELL-BEING IBU YANG MEMILIKI ANAK TUNARUNGU - Mariani, Felicia Sabrina; Ajisuksmo, Clara R.P.; Chrisnatalia, Desy (Atma Jaya Catholic University of Indonesia, 2024)
The various challenges faced by parents of deaf children can cause stress in parents. The stress experienced by parents in raising deaf children harms the parent's ability to care for children so it can have an impact on the psychological well-being of parents, especially mothers of deaf children. The aim of this research is to explore and understand the psychological well-being of mothers in caring for their deaf children. The method used in this research is narrative qualitative. The sampling method was carried out using a purposive sampling method. Data collection was carried out using a semi-structured interview method. The participants in this research were four mothers of deaf children whose ages were between six years old until twelve years old and who attended special schools. The results of this study show that the challenges in caring for a deaf child can have an impact on the mother's psychological well-being. In terms of self-acceptance, mothers accept the condition of their deaf children but tend to be dissatisfied with the care they provide for their children. The mother's attempts to broaden her understanding about deaf children and their care, demonstrate the personal growth component. In terms of positive relations with others, friends in the community are a source of enthusiasm for the mother in raising children. The demand to care for children independently encourages mothers to develop aspects of autonomy and environmental mastery. When it comes to their purpose in life, mothers have the desire to make their children become self-sufficient and able to communicate in the future.